Which addition expression has the sum 8 – 3i ?

a. (9 + 2i) + (1 – i)

b. (9 + 4i) + (–1 – 7i)

c. (7 + 2i) + (1 – i)

d. (7 + 4i) + (–1 – 7i)

Answers

Answer 1
Answer: The correct answer is B. If you drop the parenthesis and collect like terms you get 8-3i.
Answer 2
Answer:

Answer:B

Step-by-step explanation:


Related Questions

Which value must be added to the expression x2 + 12x to make it a perfect-square trinomial? 6 36 72 144
What is the length of the radius of a circle with a center at 2 + 3i and a point on the circle at 7 + 2i?
Use the substitution method to solve 3x-5y=-8 and x+2y=1
Find the missing side and round to the nearest tenth
Graph the line bu locating any two ordered pairs that satisfy the equation Y=-3x

Your bowling ball weighs 1414 pounds. How much does it weigh in ounces?

Answers

1 pound equals to 16 ounces then 16 multiply by 1414 answer is 22624

How do u write 4,000,000+3,000+50+2 in standard form

Answers

The answer to that would be 4,003,052.
4,003,052 is the answer

Farm Supply's rural mailboxes has fixed costs of $192,827.00. The selling price of a mailbox is $39.99. The average variable cost of producing a mailbox is $25.43. What is the break-even point in units?

Answers

To get the break-even point, you have to divide the fixed cost by the selling price of a mailbox less the variable cost in making a mailbox. In this case, we will have to divide $192,827.00 by $39.99 less $25.43. So, the break-even point will be 13244 units.

 

What is the value of pi?
(π)

Answers

The answer to your question is 3.14

3.14 is the value of pi.. lol

X-y+z=-4

3x+2y-z=5

-2x+3y-z=15

How do I solve this?

Answers

1)\ \ \ x-y+z=-4\ \ \ \Rightarrow\ \ \ z=-4-x+y\n\n2)\ \ \ 3x+2y-z=5 \n.\ \ \ \ \Rightarrow\ \ 3x+2y-(-4-x+y)=5 \n.\ \ \ \ \Rightarrow\ \ 3x+2y+4+x-y=5 \n.\ \ \ \ \Rightarrow\ \ 4x+y=1\n\n3)\ \ \ -2x+3y-z=15\n.\ \ \ \ \Rightarrow\ \ -2x+3y-(-4-x+y)=15\n.\ \ \ \ \Rightarrow\ \ -2x+3y+4+x-y=15\n.\ \ \ \ \Rightarrow\ \ -x+2y=11\n--------------------\n

z=-4-x+y\n.\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ and\n \left \{ {{4x+y=1\ \ \ \ } \atop {-x+2y=11\ /\cdot4}} \right. \n\n\left \{ {{4x+y=1\ \ \ \ } \atop {-4x+8y=44}} \right. \n-------\ny+8y=1+44\n9y=45\ /:9\ny=5\n\n-x+2y=11\ \ \ \Rightarrow\ \ \ x=2y-11\ \ \ \Rightarrow\ \ \ x=2\cdot5-11=-1\n\nz=-4-x+y=-4-(-1)+5=-4+1+5=2\n\nAns.\ x=-1\ \ \ and\ \ \ y=5\ \ \ and\ \ \ z=2

Simplify
-2(3x - 4y) +
5(x+3y)

Answers

Answer:

- x + 23y

Step-by-step explanation:

- 2(3x - 4y) + 5(x + 3y) \n  - 6x + 8y + 5x + 15y \n  - 6x + 5x - 8y + 23y \n  =  - x + 7y

Answer:

-x + 23y

Step-by-step explanation:

-2(3x - 4y) + 5(x+3y)

Expand the brackets.

-6x + 8y + 5x + 15y

Rearrange.

- 6x + 5x +8y + 15y

Add or subtract like terms.

- 1x + 23y